1992
DOI: 10.1016/0014-5793(92)81356-q
|View full text |Cite
|
Sign up to set email alerts
|

Processing of hepatocyte growth factor to the heterodimeric form is required for biological activity

Abstract: Hepatocyte growth factor is a plasminogen-like molecule with diverse biological effects. Although it is synthesized as a single chain polypeptide, it was originally purified as a disulfide-linked heterodimer which was generated by an internal proteolyti¢ event. Subsequent work indicated that preparations consisting largely of the monomerie form also exhibited potent activity. By using a combination of protease inhibition and site-dlrected mutagenesis+ we established that conversion of the single chain polypept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 35 publications
1
48
0
Order By: Relevance
“…Three research groups have reported that the dominant effect of plasmin was to degrade HGF to inactive fragments (39,47,56). In contrast, another group reported that plasmin treatment of conditioned media from cells transfected with an HGF expression plasmid generated increased HGF-like activity in a bioassay (57). We also found that high concentrations of plasmin extensively degrade pro-HGF (data not shown).…”
Section: Discussionmentioning
confidence: 58%
“…Three research groups have reported that the dominant effect of plasmin was to degrade HGF to inactive fragments (39,47,56). In contrast, another group reported that plasmin treatment of conditioned media from cells transfected with an HGF expression plasmid generated increased HGF-like activity in a bioassay (57). We also found that high concentrations of plasmin extensively degrade pro-HGF (data not shown).…”
Section: Discussionmentioning
confidence: 58%
“…The molecular weights of the HGF subunits produced by UB conditioned medium are consistent with activation of HGF by hydrolysis between Arg 494 and Val 495 . HGFA is a serine protease whose HGF hydrolyzing activity is blocked by the serine protease inhibitor aprotinin and the serine and cysteine protease inhibitor leupeptin, but not by the acid protease inhibitor pepstatin or the aminopeptidase inhibitor bestatin (10,11,15). HGF hydrolysis by 2.5 g of protein from UB conditioned medium was inhibited by leupeptin and aprotinin (Table I and Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Interestingly, individuals harboring a germ line met mutation develop mainly renal tumors despite the ubiquitous expression of the mutant gene (10). HGF is present in the human body mostly in the form of inactive precursor (pro-HGF) that is converted to an active factor upon local up-regulation of specific pro-HGF convertases (29). One of the most characterized pro-HGF convertases is urokinase (30), which is produced mainly if not solely by the kidney epithelium.…”
Section: Discussionmentioning
confidence: 99%